The Effect of e-WOM, Security and Trust on Purchasing Decisions of Green Lake City Housing - Amzad Samudro; Hamdan Hamdan (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
This research is about purchasing decisions for Green Lake City housing and this study aims to see the effect of e-WOM, Security and Trust on Purchasing Decisions of Green Lake City Housing and respondents who are owners of Green Lake City housing. This research is descriptive quantitative. Primary data and secondary data were obtained. Secondary data were obtained from various sources such as journalists, books and other related publications primary data obtained by distributing questionnaires to respondents. Determination of the number of samples using purposive sampling technique and will be displayed via google form to a minimum of 150 respondents. The results showed that e-WOM has a significant positive relationship with purchase decisions, security has a significant negative relationship with purchasing decisions, and trust has a significant positive relationship with purchasing decisions